Synthesis and characterization of new aromatic copoly(ether amide)s bearing 4-trifluoromethylphenyl-2, 6-diphenylpyridyl moieties in the main chain. (September 2022) - Yu, Yang-Ting; Zhao, Jing-Wei; Wei, Mei-Hong; Huang, Zhi-Hui; Liu, Xiao-Ling
A series of new aromatic fluorinated copoly(ether amide)s containing 4-(4-trifluoromethylphenyl)-2, 6-diphenylpyridyl moiety with high molecular weight were prepared by a low-temperature solution polycondensation of terephthaloyl chloride with 4-(4-trifluoromethylphenyl)-2, 6-bis(4-aminophenyl)pyridine and 1, 4-bis(4-amino-2-trifluoromethylphenoxy)benzene with various mole ratios of the two monomers ranged from 20/80 to 80/20. All polymers were amorphous and soluble in common organic solvents such as N -methyl-2-pyrrolidone, N, N -dimethylacetamide and tetrahydrofuran at room temperature or upon heating at 70 o C, and could be solution cast into transparent, tough, and flexible films with tensile strengths of 66.9–80.2 MPa, tensile moduli of 1.84–2.03 GPa, and elongations at break of 11.8–20.7%. These new polyamides displayed good thermal stability with gradually increasing of glass temperatures of 259–285 o C as an increase of the 4-(4-trifluoromethylphenyl)-2, 6-diphenylpyridyl component, the temperature at 10% weight loss of 476–505 o C, and the residue of 55–61% at 750 o C in nitrogen. They also exhibited low dielectric constants of 3.11–3.38 (1 MHz), low moisture absorption in the range of 1.43–1.75%, and high transparency with an UV–vis absorption cut-off wavelength in the 350–368 nm range.